Local adjunct effect of antimicrobial photodynamic therapy for the treatment of chronic periodontitis in type 2 diabetics: split-mouth double-blind randomized controlled clinical trial - Castro dos Santos, Nídia Cristina [UNESP]; Andere, Naira Maria Rebelatto Bechara [UNESP]; Araujo, Cássia Fernandes [UNESP]; de Marco, Andrea Carvalho [UNESP]; dos Santos, Lúcio Murilo [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Santamaria, Mauro Pedrine [UNESP] (Springer Nature, 2016)
Diabetes has become a global epidemic. Its complications can have a significant impact on quality of life, longevity, and public health costs. The presence of diabetes might impair the prognosis of periodontal treatments due to its negative influence on wound healing. Antimicrobial photodynamic therapy (aPDT) is a local approach that can promote bacterial decontamination in periodontal pockets. The aim of this study was to investigate the local effect of adjunct aPDT to ultrasonic periodontal debridement (UPD) and compare it to UD only for the treatment of chronic periodontitis in type 2 diabetic patients. Twenty type 2 diabetic patients with moderate to severe generalized chronic periodontitis were selected. Two periodontal pockets with probing depth (PD) and clinical attachment level (CAL) ≥5 mm received UPD only (UPD group) or UPD plus adjunct aPDT (UPD + aPDT group). Periodontal clinical measures were collected and compared at baseline and 30, 90, and 180 days. After 180 days of follow-up, there were statistically significant reductions in PD from 5.75 ± 0.91 to 3.47 ± 0.97 mm in the UPD group and from 6.15 ± 1.27 to 3.71 ± 1.63 mm in the UPD + aPDT group. However, intergroup analysis did not reveal statistically significant differences in any of the evaluated clinical parameters (p > 0.05). The adjunct application of aPDT to UPD did not present additional benefits for the treatment of chronic periodontitis in type 2 diabetic patients. The ClinicalTrials.gov identifier of the present study is NCT02627534.
Keywords: Antimicrobial therapy; Chronic periodontitis; Diabetes mellitus; Low-level laser therapy; Periodontal pocket; Photodynamic therapy